MANAJEMEN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR NEGERI PODOSUGIH 01 KOTA PEKALONGAN - Hikmatullaila; Muhdi; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Independent Curriculum is a curriculum that provides flexibility and focuses on essential materials to develop student competencies as lifelong learners with Pancasila characters. The implementation of the Independent Curriculum requires effective management from the school, especially the principal who plays a central role in school management. The principal applies management in the implementation of the independent curriculum to achieve the goals of student learning development. The principal has a strong function in planning, organizing, implementing and supervising the implementation of the independent curriculum. Podosugih 01 Elementary School is one of the elementary schools that has implemented the Independent Curriculum. The management of the principal of Podosugih 01 Elementary School in the successful implementation of the independent curriculum is related to the development of an optimally designed curriculum. This study aims to describe and analyze the planning, organizing, implementing and supervising the implementation of the Independent Curriculum at Podosugih 01 Elementary School, Pekalongan City. The approach used in this study is a qualitative approach. Data collection techniques use interviews, observations, and documentation. Data analysis used in this study includes data collection, data reduction, data presentation and drawing conclusions/verification. This study used two types of triangulation, namely source triangulation and technique triangulation to test the validity of the data. The results of the study showed that: 1) The planning implemented by the principal in the implementation of the independent curriculum at SD Negeri Podosugih 01 has been carried out systematically in accordance with the planning stages, namely the identification of student needs is carried out through an initial assessment. Another thing used in identifying student needs besides the initial assessment is the achievement of educational report cards. 2) The organization implemented by the principal in the implementation of the independent curriculum at SD Negeri Podosugih 01 has been in accordance with the procedure, namely with the presence of a curriculum development team at the school, the principal determines the division of teaching tasks and the preparation of lesson schedules, management of human resources and the fulfillment of learning facilities and infrastructure. 3) The implementation implemented by the principal in the implementation of the independent curriculum at SD Negeri Podosugih 01 is effective. The main objective to be achieved in the implementation of intracurricular, co-curricular and extracurricular learning is the realization of the vision and mission of SD Negeri Podosugih 01. 4) Supervision implemented by the principal in the implementation of the independent curriculum at SD Negeri Podosugih 01 is effective as seen from the implementation of existing procedures. Monitoring of teaching and learning activities every day, then supervising the teachers who teach, and providing the results of teacher performance assessments. Keywords: Principal Management, Implementation, Independent Curriculum.